2016
DOI: 10.1101/cshperspect.a023630
|View full text |Cite
|
Sign up to set email alerts
|

Potential Pathways of Abnormal Tau and α-Synuclein Dissemination in Sporadic Alzheimer's and Parkinson's Diseases

Abstract: Experimental data indicate that transneuronal propagation of abnormal protein aggregates in neurodegenerative proteinopathies, such as sporadic Alzheimer's disease (AD) and Parkinson's disease (PD), is capable of a self-propagating process that leads to a progression of neurodegeneration and accumulation of prion-like particles. The mechanisms by which misfolded tau and a-synuclein possibly spread from one involved nerve cell to the next in the neuronal chain to induce abnormal aggregation are still unknown. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(104 citation statements)
references
References 239 publications
(367 reference statements)
3
100
0
1
Order By: Relevance
“…In line with this, the granular insula connects to isocortical somatosensory and cingulate cortex and is affected in later stages of the disease [38]. Thus the cytoarchitecture and the connectivity of the insular subregions could provide a framework for the understanding of dissemination of α-synuclein pathology throughout the brain [11,21]. Considering the anterior insula connectivity, α-synuclein pathology and cell death in the agranular insula may also contribute to autonomic, cognitive and psychiatric symptoms in PD(D) and DLB [52].…”
Section: Discussionmentioning
confidence: 75%
“…In line with this, the granular insula connects to isocortical somatosensory and cingulate cortex and is affected in later stages of the disease [38]. Thus the cytoarchitecture and the connectivity of the insular subregions could provide a framework for the understanding of dissemination of α-synuclein pathology throughout the brain [11,21]. Considering the anterior insula connectivity, α-synuclein pathology and cell death in the agranular insula may also contribute to autonomic, cognitive and psychiatric symptoms in PD(D) and DLB [52].…”
Section: Discussionmentioning
confidence: 75%
“…Beyond the medial temporal lobe, AD post-mortem studies have established that neurofibrillary tangles within the preoptic area of the hypothalamus correlate with the severity of prior fragmented sleep (Lim et al, 2014). Interestingly, tau deposition is also present in other sleep-regulating areas such as the locus coeruleus and basal forebrain and can be observed even in cognitively normal older adults (Braak and Del Tredici, 2016; Braak et al, 2011; Stern and Naidoo, 2015). This leads to the currently untested hypothesis that tau within these regions may trigger sleep abnormalities years before degenerative disease onset and, if such sleep disruption is specific, could serve as an early diagnostic biomarker (Holth et al, 2016).…”
Section: What About Sleep Changes With Age?mentioning
confidence: 99%
“…In HD, neurons in different brain regions accumulate abnormal deposits of misfolded protein, a histopathological hallmark shared with other proteinopathies, such as AD and PD (Braak & Del Tredici, 2016;Saudou & Humbert, 2016). Recent findings suggested that pathogenic proteins, such as beta-amyloid/Tau in AD and alphasynuclein in PD, can spread in a prion-like fashion via selective functionally connected neural networks, triggering specific clinical phenotypes of brain disorders (Brettschneider, Del Tredici, Lee, & Trojanowski, 2015;Jucker & Walker, 2011;Raj, Kuceyeski, & Weiner, 2012).…”
Section: Neurobiological and Clinical Considerationsmentioning
confidence: 99%